Centre characteristics and procedure-related factors have an impact on outcomes of allogeneic transplantation for patients with CLL: a retrospective analysis from the European Society for Blood and Marrow Transplantation (EBMT) - Schetelig, Johannes; Dreger, Peter (British journal of haematology, 2017)
The best approach for allogeneic haematopoietic stem cell transplantations (alloHCT) in patients with chronic lymphocytic leukaemia (CLL) is unknown. We therefore analysed the impact of procedure- and centre-related factors on 5-year event-free survival (EFS) in a large retrospective study. Data of 684 CLL patients who received a first alloHCT between 2000 and 2011 were analysed by multivariable Cox proportional hazards models with a frailty component to investigate unexplained centre heterogeneity. Five-year EFS of the whole cohort was 37% (95% confidence interval [CI], 34-42%). Larger numbers of CLL alloHCTs (hazard ratio [HR] 0·96, P = 0·002), certification of quality management (HR 0·7, P = 0·045) and a higher gross national income per capita (HR 0·4, P = 0·04) improved EFS. In vivo T-cell depletion (TCD) with alemtuzumab compared to no TCD (HR 1·5, P = 0·03), and a female donor compared to a male donor for a male patient (HR 1·4, P = 0·02) had a negative impact on EFS, but not non-myeloablative versus more intensive conditioning. After correcting for patient-, procedure- and centre-characteristics, significant variation in centre outcomes persisted. In conclusion, further research on the impact of centre and procedural characteristics is warranted. Non-myeloablative conditioning appears to be the preferable approach for patients with CLL.